2022
DOI: 10.1039/d2ra05531g
|View full text |Cite
|
Sign up to set email alerts
|

One pot tandem dehydrogenative cross-coupling of primary and secondary alcohols by ruthenium amido-functionalized 1,2,4-triazole derived N-heterocyclic carbene complexes

Abstract: Three neutral 1,2,4-triazole derived amido-functionalized N-heterocyclic ruthenium carbene complexes efficiently catalyzed one-pot tandem dehydrogenative cross-coupling of primary and secondary alcohols via a metal–ligand non-cooperative pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…92 The methodology that has been used is B3LYP-D3 functional along with the basis set SDD for Ru atoms and 6-31G* 80,81 for other atoms. This is a time-tested methodology for the Ru catalyst and also has reproduced several experimental spectral features, 82 offering confidence in the methodology. The single point energies were computed on the optimized geometries with the def2-TZVP basis set for all atoms.…”
Section: Computational Detailsmentioning
confidence: 78%
“…92 The methodology that has been used is B3LYP-D3 functional along with the basis set SDD for Ru atoms and 6-31G* 80,81 for other atoms. This is a time-tested methodology for the Ru catalyst and also has reproduced several experimental spectral features, 82 offering confidence in the methodology. The single point energies were computed on the optimized geometries with the def2-TZVP basis set for all atoms.…”
Section: Computational Detailsmentioning
confidence: 78%
“…34 As observed, the Ru-6 complex having a pendant thiazolyl group, Scheme 6 Ruthenium-catalysed cross b-alkylation of secondary and primary alcohols (ref. [30][31][32][33][34][35][36][37][38][39][40].…”
Section: B-alkylation Of Secondary Alcohols With Primary Alcoholsmentioning
confidence: 99%
“…In 2022, Ghosh and co-workers proposed cross-coupling of secondary and primary alcohols catalyzed by ruthenium complexes of amido-functionalized 1,2,4-triazole-derived NHC ligands, Ru-10 ( A , B , C ). 39 DFT calculations using the Ru-10B system revealed that the reaction proceeded via three steps, namely, nucleophilic substitution of chloride ions by alcohols, followed by dehydrogenation of both the alcohols to form carbonyls, and finally, hydrogenation via 1,4-addition of the α,β-unsaturated carbonyl compound, which led to the desired product.…”
Section: Cross-coupling Of Alcoholsmentioning
confidence: 99%